Combined Methylome, Transcriptome and Proteome Analyses Document Rapid Acclimatization of a Bacterium to Environmental Changes - Srivastava, Abhishek; Murugaiyan, Jayaseelan; Garcia, Juan A. L.; De Corte, Daniele; Hoetzinger, Matthias; Eravci, Murat; Weise, Christoph; Kumar, Yadhu; Roesler, Uwe; Hahn, Martin W.; Grossart, Hans-Peter (Frontiers in Microbiology, 2020)
Polynucleobacter asymbioticus strain QLW-P1DMWA-1T represents a group of highly successful heterotrophic ultramicrobacteria that is frequently very abundant (up to 70% of total bacterioplankton) in freshwater habitats across all seven continents. This strain was originally isolated from a shallow Alpine pond characterized by rapid changes in water temperature and elevated UV radiation due to its location at an altitude of 1300 m. To elucidate the strain’s adjustment to fluctuating environmental conditions, we recorded changes occurring in its transcriptomic and proteomic profiles under contrasting experimental conditions by simulating thermal conditions in winter and summer as well as high UV irradiation. To analyze the potential connection between gene expression and regulation via methyl group modification of the genome, we also analyzed its methylome. The methylation pattern differed between the three treatments, pointing to its potential role in differential gene expression. An adaptive process due to evolutionary pressure in the genus was deduced by calculating the ratios of nonsynonymous to synonymous substitution rates for twenty Polynucleobacter spp. genomes obtained from geographically diverse isolates. The results indicate purifying selection.